Apoptotic extracellular vesicles derived from human dental pulp stem cells facilitate periodontal tissue regeneration - Junyi Xia; Zeyu Zhang; Jinlong Weng; Guanxiong Zhu; Zidan Xu; Liting Zeng; Janak Lal Pathak; Lina Yu (BMC Oral Health)
Abstract Objective Apoptotic extracellular vesicles (ApoEVs) derived from human dental pulp stem cells (hDPSCs) are subcellular structures released during programmed cell death. These vesicles carry rich biological information and regulatory potential, and have demonstrated significance in regulating cell behavior and tissue repair. Human periodontal ligament stem cells (hPDLSCs) are key to regenerating periodontal tissue, and their osteogenic differentiation ability directly influences the repair and reconstruction of periodontal bone tissue. However, the potential of ApoEVs derived from human dental pulp stem cells (hDPSCs-ApoEVs) to regulate the osteogenic differentiation of hPDLSCs remains unexplored. This study aims to investigate the effects of hDPSCs-ApoEVs on the osteogenic differentiation of hPDLSCs, offering new insights and methods for treating periodontal bone tissue injuries, with important scientific and clinical implications. Methods hDPSCs-ApoEVs were isolated via ultracentrifugation and characterized by transmission electron microscopy (TEM), dynamic light scattering (DLS), and Western blot. In vitro, hPDLSCs were treated with hDPSCs-ApoEVs to determine whether the vesicles could enter hPDLSCs and to assess the proliferation, migration, and osteogenic potential of hPDLSCs. In vivo, a rat periodontal bone defect model was established, with local injections of hDPSCs-ApoEVs or PBS administered every other day. After 6 weeks, the maxillae were collected and analyzed using micro-CT and histological staining. Results In vitro, hDPSCs-ApoEVs promoted the migration and osteogenic differentiation of hPDLSCs. In vivo, treatment with hDPSCs-ApoEVs can enhance the recovery of periodontal bone defects in rats. Conclusion hDPSCs-ApoEVs play a significant role in promoting bone regeneration, suggesting their potential as a promising cell-free therapeutic strategy for periodontal bone tissue regeneration.